Continuity in the Kindergarten and Primary School in the Implementation of the Contents of Laying the Foundations of Individual Value Attitude to Their Own Health - Pyechka, Larysa (Journal of Vasyl Stefanyk Precarpathian National University, 2016)
In the article are highlighted the results of theoretical analysis of continuity in the kindergarten and primary school in the implementation of the contents of laying the foundations of individual value attitude to their own health. Researcher reveals the pedagogical theories of scientists to study the problem of succession. For depth scientific analysis and practical implementation of the process under study the emphasis is made on identifying scientific aspects for developing children's healthy lifestyle